1992
DOI: 10.1155/1992/36147
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Peripherally Induced Tolerance to Established Skin Allografts in Immunologically Reconstituted Scid Mice

Abstract: The mechanism by which the antigen-specific immune system distinguishes between foreign antigens (toward which it mounts an immune response) and self-antigens (of which it is tolerant) is not completely understood. Studies using “superantigens” and transgenic mice have allowed investigations into some of the mechanisms of clonal deletion, anergy, and peripheral tolerance. In the present report, we have attempted to develop a new model system to investigate the possible mechanism(s) of peripheral tolerance to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…These observations have led us to hypothesize that allograft rejection in tolerized mice is due to the emergence of alloreactive thymic emigrants in a milieu in which declining levels of anti-CD154 mAb preclude the blockade of costimulation (5,18). In support of this hypothesis, we (25) and others (26,27) have shown that hemopoietic stem cell reconstitution of mice with successful intact allografts will lead to the rejection of these grafts in the absence of surgical trauma or other forms of activation, but direct evidence that this is due to newly developed T cells is lacking.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…These observations have led us to hypothesize that allograft rejection in tolerized mice is due to the emergence of alloreactive thymic emigrants in a milieu in which declining levels of anti-CD154 mAb preclude the blockade of costimulation (5,18). In support of this hypothesis, we (25) and others (26,27) have shown that hemopoietic stem cell reconstitution of mice with successful intact allografts will lead to the rejection of these grafts in the absence of surgical trauma or other forms of activation, but direct evidence that this is due to newly developed T cells is lacking.…”
mentioning
confidence: 60%
“…This observation is of particular interest in light of our data demonstrating that graft rejection is also associated with the activation of CD8 ϩ alloreactive cells. We (25) and others (26,27) have shown that some of the T cells that develop in the thymus of mice bearing a healed-in allograft have not been tolerized to that graft. It has also been reported in nonhuman primates tolerized with anti-CD154 mAb that islet allograft maintenance requires periodic retreatment with the Ab (41).…”
Section: Discussionmentioning
confidence: 95%
“…However, this view also has been challenged in several ways. As early as 1979, it was shown that skin grafts that had been grafted onto nude mice before reconstituting the recipients with a thymus graft were rejected by the newly generated T cells (11), and similar results were later obtained in SCID and RAG-KO mice (10,15). Furthermore, grafts given to chicken or sheep embryos before the development of immunocompetence also were rejected when the animals developed immune competence (12)(13)(14).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, we were left with the question of what allowed the newly developing T cells to discriminate between the long-healed skin of the male donor and the normal peripheral tissues of the recipient, rejecting the former and becoming tolerant of the latter. In other studies of "well-healed" MHC or multiple minor mismatched grafts (10,11,15), the stimulus for rejection could have been cross-reactive environmental Ags (which may themselves be associated with danger signals) rather than the grafts themselves, making these studies difficult to interpret. To resolve these difficulties, Bingaman et al (10) suggested that studies with H-Y may be enlightening.…”
mentioning
confidence: 99%
“…These data demonstrate that ''danger or injury'' is not sufficient to stimulate an alloresponse and, in line with the concept proposed by Sir Macfarlane Burnet half a century ago (4), suggest an alternative view that the trigger for both triggering and bridging the innate and adaptive response involves alloantigen. Although the nature of the molecular sensors allowing recipient's immune effectors to sense allogeneic nonself remains yet to be identified, these data could account for why grafts are not ignored by the adaptive immune system even after inflammation has long subsided (5).…”
mentioning
confidence: 99%